(untitled) (Cardiovascular Journal, 2012)
Background: Inflammation has been shown to play a role in atherosclerosis and acute coronary syndrome. This study was carried out to evaluate the relationship between baseline white blood cell (WBC) count and C-reactive protein (CRP) with angiographic severity of coronary artery disease in patients with acute coronary syndrome and to identify those subsets of patients with acute coronary syndrome who may need to undergo invasive or conservative strategies. Method: A total of 100 patients with acute coronary syndrome including unstable angina, non-ST elevated myocardial infarction & ST elevated myocardial infarction were evaluated in National Institute of Cardiovascular Disease (NICVD), Dhaka with a view to correlate angiographic findings, C-reactive protein and WBC count. Results: This study observed that either raised WBC count or raised CRP independently and combination of both WBC count and CRP elevation were significantly associated with more severe coronary artery disease. Either raised WBC count or raised CRP or combination of raised WBC count and CRP were significant predictor of multivessel disease and high stenosis score. Conclusion: Elevation of WBC count and CRP in patients with acute coronary syndrome are associated with severe coronary disease. WBC count and CRP can be used as a new and even simpler tool for risk stratification in acute coronary syndrome. DOI: http://dx.doi.org/10.3329/cardio.v5i1.12209 Cardiovasc. j. 2012; 5(1): 23-29